A review of advanced optimization strategies for fermentative biohydrogen production processes - Mohd Farid, Bin Atan; MOHAMAD AFIQ, MOHD ASRUL; Hafizah, Abdul Halim Yun; Josephine, Chang Hui Lai (ELSEVIER, 2022)
The inability of statistical optimization to represent the dynamic interaction of the biohydrogen process, which is highly non-linear and complicated, has been identified. However, incorporating a data-driven black-box model could overcome the limitations of conventional methods to provide correct responses rapidly and cost-effective modeling. Despite significant reports on the optimization of hydrogen production from fermentation, fewer studies have been made for the case using artificial intelligence algorithms. As a result, critical and extensive analyses of previous works are conducted to develop a general methodological framework for advanced response optimization.